How Workplace Bullying Jeopardizes Employees’ Life Satisfaction: The Roles of Job Anxiety and Insomnia - Nauman, Shazia; Malik, Sania Zahra; Jalil, Faryal (Frontiers in Psychology, 2019)
Drawing on Conservation of resources (COR) theory, this study examined the underlying mechanism through which workplace bullying (WB) affects employees’ life satisfaction via job- related anxiety and insomnia. Time-lagged data were collected at two points in time from 211 doctor interns working in various hospitals in Pakistan. Results fully support a proposed serial multiple-mediator model. Workplace bullying is indirectly related to life satisfaction via job-related anxiety and insomnia. This study provides evidence of a spillover effect as to how workplace bullying increases employees’ job-related anxiety which in turn leads to insomnia resulting in reduced employees’ life satisfaction. The present study extends research on workplace bullying to display its theoretical as well as empirical effects on life satisfaction. It demonstrates that workplace bullying as an occupational and psychological stressor has multiple effects on employees’ life satisfaction through a serial mediation model in the context of a developing country. It further explains that workplace bullying not only affects an employee’s workplace behaviors but also extends to the employee’s over-all life satisfaction. Keywords: Workplace bullying, job-related anxiety, insomnia, life satisfaction.